Métaphysique du mariage d’après Thomas d’Aquin - Oliva, Adriano (Revue des sciences philosophiques et théologiques, 2017)
To respond to the criticisms of Henry Donneaud, we develop here our previous study on the proper end of marriage according to St. Thomas, drawing support from a greater number of texts. On the one hand, we show the accuracy of our exegesis of these texts and the coherence of our study with the metaphysical teaching of the Aquinate. On the other hand, we demonstrate that, according to St. Thomas, procreation cannot be the proper end of marriage, but that it is its very essence, the role of end being exercised by the friendship of the spouses and the indivisible union of their hearts and minds.